2005
DOI: 10.1073/pnas.0509736102
|View full text |Cite
|
Sign up to set email alerts
|

Increase in TNF-α and inducible nitric oxide synthase-expressing dendritic cells in psoriasis and reduction with efalizumab (anti-CD11a)

Abstract: We find that CD11c ؉ cells with many markers of dendritic cells (DCs) are a major cell type in the skin lesions of psoriasis. These CD11c ؉ cells, which are evident in both epidermis and dermis, are the sites for the expression of two mediators of inflammation, inducible nitric oxide synthase (iNOS) and TNF-␣ in diseased skin. These cells express HLA-DR, CD40, and CD86, lack the Langerin and CD14 markers of Langerhans cells and monocytes, respectively, and to a significant extent express the DC maturation mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
379
0
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 432 publications
(416 citation statements)
references
References 33 publications
(34 reference statements)
18
379
0
9
Order By: Relevance
“…Since they also expressed CD83 (Fig. 3C), TNF-a and iNOS, they could resemble Tip-DCs previously described in mice [3][4][5] and humans [22]. …”
supporting
confidence: 71%
See 1 more Smart Citation
“…Since they also expressed CD83 (Fig. 3C), TNF-a and iNOS, they could resemble Tip-DCs previously described in mice [3][4][5] and humans [22]. …”
supporting
confidence: 71%
“…T-cell and DC infiltration, resulted in decreased inflammation in the skin and a reduced number of Tip-DCs [22]. It is likely that reduced CD8 1 T-cell infiltration into skin can help to minimize monocyte recruitment and their inflammatory effects on monocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is likely that anti-IL-12p40 effectively blocked the action of intracutaneous IL-12 and IL-23, from lesional APCs on lesional Th1 cells. According to recent reports, CD11c ϩ DCs are greatly increased in psoriatic skin compared with uninvolved skin, and the number of CD11c ϩ cells exceeds the number of CD3 ϩ T cells (53). In patients treated with efalizumab (anti-CD11a), CD11c ϩ cells in psoriatic skin significantly decreased at 2 wk posttreatment, probably because efalizumab directly inhibits the migration of these cells (53).…”
Section: Discussionmentioning
confidence: 99%
“…According to recent reports, CD11c ϩ DCs are greatly increased in psoriatic skin compared with uninvolved skin, and the number of CD11c ϩ cells exceeds the number of CD3 ϩ T cells (53). In patients treated with efalizumab (anti-CD11a), CD11c ϩ cells in psoriatic skin significantly decreased at 2 wk posttreatment, probably because efalizumab directly inhibits the migration of these cells (53). In our study, as shown in Table I, the number of CD11c ϩ cells in both responder groups decreased, but this decrease was not yet statistically significant at 2 wk posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…A key feature of psoriasis is the abnormal activation of dendritic cell (DC) subsets in the dermal compartment leading to the downstream T-cell-mediated autoimmune cascade [4]. A role for plasmacytoid DCs (pDCs) producing type I IFNs appears to be central in this process.…”
Section: Introductionmentioning
confidence: 99%